PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK, TALK AND WRITE DENGAN TEKNIK TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA DI KELAS VII.3 SMP NEGERI 3 TAMBANG - ', Rusnita; Fauziah, Yuslim; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted aiming to student learning outcomes through the implementation of cooperative learning model think, talk and write with a talking stick-in-class engineering VII.3 SMP Negeri 3 Tambang on the material Ecosystem and Environmental Pollution. This research is a classroom action research conducted in two cycles in April and May 2016. The subjects were VII.3 grade students of SMP Negeri 3 Tambang 2015/2016 school year totaling 29 people consisting of 11 female students and 18 students man. Parameter study is the result of learning of students consisting of absorption and mastery learning. The results of student learning based on the average absorption of students in the first cycle is 78.10 and the second cycle increased to 86.37. Mastery learning students in the first cycle is 79.31% and the second cycle increased to 89.65%. From the results of this study concluded that the implementation of cooperative learning model think, talk and write with a talking stick technique can improve learning outcomes of students in the class VII.3 IPA SMP Negeri 3 Tambang.Keywords: Model cooperative think, talk and write, Mechanical talking stick, student.